Symbolic landscapes: popular catholicism and the myth of the “Green Flags” in the Pilgrimage of the “Lord of Bonfim” in Araguacema, Tocantins - Carvalho, José Rodrigues (Geografares, 2014)
This text aims to show the relationship between the religion and the landscape, based on the myth of the “Green Flags” in the imaginary of Popular Catholicism, which created and keeps the “Lord of Bonfim” pilgri-mage, in Araguacema, Tocantins. We discuss the topic Religion and landscape from data obtained in field work in the perspective of humanistic cultural geography. The Pilgrimage’s landscape holds a number of symbols that represent a universe of meanings of popular catholicism in a game that establishes the rela-tionship between the living area and memories, in which the images take the place of straight perceptions.